A HIGH-FAT, HIGH-SUGAR DIET INDUCES INSULIN-LIKE GROWTH FACTOR 2 HYPER- METHYLATION IN MALE WISTAR RATS - Willmer, Tarryn; Myataza, Asive; Patel, Oelfah; Johnson, Rabia; Pheiffer, Carmen (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE The prevalence of obesity and insulin resistance (IR) has increased at an exponential rate worldwide. Although several mechanisms such as dysregulation of the epigenome have been implicated, the disease pathophysiology remains to be fully elucidated. The primary objective of this study was to elucidate DNA methylation profiles and gene regulatory networks that are altered in the skeletal muscle (SM) during the development of obesity and IR in male Wistar rats. METHODOLOGY Male Wistar rats (n=20) were fed either a high-fat, high- sugar (HFHS) or a standard diet (STD) for 12 weeks. SM was harvested for histology, gene expression measured using RT2 Profiler™ PCR arrays and Taqman® assays and global and gene-specific DNA methylation were quantified using pyrosequencing. RESULTS Rats in the HFHS group gained more weight (567.5 ± 8.8 vs 474.0 ± 10.5 g, p<0.0001) and had increased insulin concentrations (6.1 ± 0.9 vs 3.8± 0.6 ng/ml, p<0.05) compared to the STD-fed rats, while no histological differences were noted. Increased expression of Insulin-like growth factor 2 (IGF2) was associated with HFHS diet exposure. Whilst no global DNA methylation changes were observed, we identified hypermethylation of an intronic CpG site within IGF2 (p<0.01). In silico analysis identified binding sites for transcription factors CCCTC-binding factor (CTCF), myogenin and myoblast determination protein 1 (MYOD) within close proximity to the hypermethylated CpG. CONCLUSION This study provides information about dysregulated DNA methylation and gene expression signatures during the progression of obesity and IR in SM.